Awareness during anaesthesia for surgery requiring evoked potential monitoring: A pilot study - Korula, Pritish J.; Mariappan, Ramamani; James, Justin P.; Kumar, Prashant; Korula, Grace (Journal of Neuroanaesthesiology and Critical Care, 2017)
Background: Evoked potential monitoring such as somatosensory-evoked potential (SSEP) or motor-evoked potential (MEP) monitoring during surgical procedures in proximity to the spinal cord requires minimising the minimum alveolar concentrations (MACs) below the anaesthetic concentrations normally required (1 MAC) to prevent interference in amplitude and latency of evoked potentials. This could result in awareness. Our primary objective was to determine the incidence of awareness while administering low MAC inhalational anaesthetics for these unique procedures. The secondary objective was to assess the adequacy of our anaesthetic technique from neurophysiologist’s perspective. Methods: In this prospective observational pilot study, 61 American Society of Anesthesiologists 1 and 2 patients undergoing spinal surgery for whom intraoperative evoked potential monitoring was performed were included; during the maintenance phase, 0.7–0.8 MAC of isoflurane was targeted. We evaluated the intraoperative depth of anaesthesia using a bispectral (BIS) index monitor as well as the patients response to surgical stimulus (PRST) scoring system. Post-operatively, a modified Bruce questionnaire was used to verify awareness. The adequacy of evoked potential readings was also assessed. Results: Of the 61 patients, no patient had explicit awareness. Intraoperatively, 19 of 61 patients had a BIS value of above sixty at least once, during surgery. There was no correlation with PRST scoring and BIS during surgery. Fifty-four out of 61 patient’s evoked potential readings were deemed ‘good’ or ‘fair’ for the conduct of electrophysiological monitoring. Conclusions: This pilot study demonstrates that administering low MAC inhalational anaesthetics to facilitate evoked potential monitoring does not result in explicit awareness. However, larger studies are needed to verify this. The conduct of SSEP electrophysiological monitoring was satisfactory with the use of this anaesthetic technique. However, the conduct of MEP monitoring was satisfactory, only in patients with Nurick Grade 1 and 2. The MEP response was poor in patients with Nurick Grade 4 and 5.
Keywords: Anaesthesia; anaesthesia depth monitor; awareness; evoked potential monitoring; spine